Metalcutting sheet metal stamping dies & presses - Cook, Jerome T.; Green, Richard G. (Fundamental manufacturing processes, 1997)
This programme explains stamping dies and the processes which form parts from sheet metal. Examples of many different die operations, such as shearing, blanking, drawing, and flanging are given. It examines the different types of single station and multiple station dies, and explains how they function. Important factors in formability, and the types and severity of deformation that may occur at various points on a stamped part, and stamping analysis techniques are discussed.